2019
DOI: 10.1182/blood.2019000578
|View full text |Cite
|
Sign up to set email alerts
|

PHF19 promotes multiple myeloma tumorigenicity through PRC2 activation and broad H3K27me3 domain formation

Abstract: Polycomb repressive complex 2 (PRC2) dysregulation is associated with proliferation of hematological malignancies. Ren et al elucidate the mechanisms of PRC2 in multiple myeloma (MM), demonstrating that malignant progression of MM is associated with overexpression of PHF19, a PRC2-associated factor that enhances its gene-regulatory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 79 publications
9
73
1
Order By: Relevance
“…shRNA induced cells showed knockdown (KD) of >90% PHF19 RNA and protein relative to the control after 72 hrs and 168 hrs for the JJN3 and ARP1 cell lines, respectively (Figure 4a and 4b). KD of PHF19 led to significant inhibition of proliferation in the JJN3 and ARP1 MM cell lines compared to scrambled shRNA control (Figure 4c-d) confirming the recent finding of PHF19's effect on proliferation in MM cell lines 27 . To identify the mechanism of growth inhibition, we performed cell cycle analysis and observed a significant arrest of MM cells in the G0/G1 stage with PHF19 KD compared to the scrambled control shRNA (Supplemental Figure 3a).…”
Section: Knockdown Of Phf19 Leads To Decreased Proliferation Throughsupporting
confidence: 86%
“…shRNA induced cells showed knockdown (KD) of >90% PHF19 RNA and protein relative to the control after 72 hrs and 168 hrs for the JJN3 and ARP1 cell lines, respectively (Figure 4a and 4b). KD of PHF19 led to significant inhibition of proliferation in the JJN3 and ARP1 MM cell lines compared to scrambled shRNA control (Figure 4c-d) confirming the recent finding of PHF19's effect on proliferation in MM cell lines 27 . To identify the mechanism of growth inhibition, we performed cell cycle analysis and observed a significant arrest of MM cells in the G0/G1 stage with PHF19 KD compared to the scrambled control shRNA (Supplemental Figure 3a).…”
Section: Knockdown Of Phf19 Leads To Decreased Proliferation Throughsupporting
confidence: 86%
“…Recent follow-up studies have finely deciphered the mechanisms implicating hPL3L/PHF9L and hPCL3S in several cancer types including glioblastomas [45], hepatocellular carcinomas [25], multiple myelomas [46], and prostate (this study). Despite the low number of studies, a clear-cut situation seems to emerge with two different mechanisms for hPCL3L/PHF19 and hPCL3S.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, recruitment of PRC2 to DNA regions of target genes to catalyze the methylation of lysine 27 on histone 3 (H3K27me3), are essential for controlling the developmental gene expression and maintaining cell specification (Kouznetsova et al, 2019). Aberrant expression of PHF19 has been implicated in regulating the pathogenesis and progression of a wide range of cancers, including melanoma (Ghislin et al, 2012), hepatocellular carcinoma (Xu et al, 2015;Cai et al, 2018), glioma (Lu et al, 2018), glioblastoma (Deng et al, 2018), multiple myeloma (Ren et al, 2019). In our previous publication, we have found that patients with higher expression of PHF19 are associated with shorter progressionfree survival (PFS) than that with lower PHF19 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this increase in expression correlated with cancer progression (Wang et al, 2004). After that, accumulating evidence uncover the oncogenic role of PHF19 in a wide range of tumors (Ghislin et al, 2012;Xu et al, 2015;Lu et al, 2018;Tao et al, 2018b;Ren et al, 2019). For instance, PHF19 knockdown reduces the cell proliferation rate and increases the migration capacities of melanoma cells (Ghislin et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation